Marx's capital and capitalism markets in a socialist alternative - Zarembka, Paul (Emerald, 2001)
The political economist N. Sieber wrote a book in 1871 in part summarizing Marx's value theory compared to Ricardo's, and Marx himself favourably commented on the interpretation. Here, Sieber's Russian text on Marx is translated, joined with an introductory preface by James D. White and an article by David Smith on Sieber's understanding of value theory. Alfredo Saad-Filho develops implications of introducing a more refined discussion of the composition of capital into Zarembka's work on accumulation of capital in the previous issue, while the tendency of the profit rate under two alternative criteria for technical choice is analyzed by Cheol-Soo Park. The regulation of social relations by markets is criticized by Martyn Konings as being antithetical to socialism. Ideology provides our representations of the world we live in and Thierry Suchere connects the symbolic dimension to economic activity. Close links between Wittgenstein's philosophy and Sraffa's political economy as both embodying bourgeois ideology are developed by Jorgen Sandemose. Finally, the Stalinist ideological formation as a key component of Soviet history is developed from a Marxist perspective by Charles Bettelheim.
Keywords: Marxian economics.; Socialism.; elektronické knihy; electronic books